2019
DOI: 10.3390/su11154220
|View full text |Cite
|
Sign up to set email alerts
|

Scenario Analysis of Carbon Emissions in the Energy Base, Xinjiang Autonomous Region, China

Abstract: The realization of carbon emissions peak is important in the energy base area of China for the sustainable development of the socio-economic sector. The STIRPAT model was employed to analyze the elasticity of influencing factors of carbon emissions during 1990-2010 in the Xinjiang autonomous region, China. The results display that population growth is the key driving factor for carbon emissions, while energy intensity is the key restraining factor. With 1% change in population, gross domestic product (GDP) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Wang et al (2019) found that based on the continuous economic development and urbanization process, CEs in Guangdong will maintain a growth trend in 2015-2030. Qin et al (2019) predicted the changes of CEs in Xinjiang and found that its CEs will peak at 626. 21-662.25Mtons in 2030-2040 predicted the CEs reduction in the Beijing-Tianjin-Hebei region up to 2030, and found that energy intensity is the key driver for achieving CEs reduction targets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al (2019) found that based on the continuous economic development and urbanization process, CEs in Guangdong will maintain a growth trend in 2015-2030. Qin et al (2019) predicted the changes of CEs in Xinjiang and found that its CEs will peak at 626. 21-662.25Mtons in 2030-2040 predicted the CEs reduction in the Beijing-Tianjin-Hebei region up to 2030, and found that energy intensity is the key driver for achieving CEs reduction targets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the transformation of resource advantage into an economic advantage and technological progress of resource and energy-intensive industries will be the linchpin to achieving socioeconomic sustainable development in Xinjiang [34]. This also means that the energy-intensive industries play a decisive role in realizing the decoupling of carbon emissions in Xinjiang [6]. In the future, the mitigation of carbon emissions in Xinjiang should be by reducing the proportion of energy-intensive industries' GDP, increasing investment, and improving energy efficiency to decouple economic development from carbon emissions increase.…”
Section: Decoupling State On Sectorsmentioning
confidence: 99%
“…Greenhouse gases are regarded as the key reason for global warming [3], while carbon emissions from fossil fuel combustion are regarded as the direct contributor to greenhouse gases [4]. In the context of global warming, carbon emissions have become a strong focus in academia [5,6]. Given that, countries have joined in the procession of carbon emissions mitigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding carbon emissions in Xinjiang, economic growth and population scale were confirmed as important contributors to increased carbon emissions, while the decrease of energy intensity was highlighted for curbing carbon emissions [7,39]. But the approach to carbon emissions reduction will depend on effective mitigation strategy of each sector; however, variable energy intensities of different sectors can impact the magnitude of carbon reduction.…”
Section: Introductionmentioning
confidence: 99%